Eddy Wake Generation From Broadband Currents Near Palau. Issue 7 (18th July 2019) - MacKinnon, Jennifer A.; Alford, Matthew H.; Voet, Gunnar; Zeiden, Kristin L.; Shaun Johnston, T. M.; Siegelman, Mika; Merrifield, Sophia; Merrifield, Mark
Abstract: Wake eddies are frequently created by flow separation where ocean currents encounter abrupt topography in the form of islands or headlands. Most previous work has concentrated on wake eddy generation by either purely oscillatory (usually tidal) currents, or quasi‐steady mean flows. Here we report measurements near the point of flow separation at the northern end of the Palau island chain, where energetic tides and vertically sheared low‐frequency flows are both present. Energetic turbulence measured near the very steeply sloping ocean floor varied cubically with the total flow speed (primarily tidal). The estimated turbulent viscosity suggests a regime of flow separation and eddying wake generation for flows that directly feel this drag. Small‐scale (∼1 km), vertically sheared wake eddies of different vorticity signs were observed with a shipboard survey on both sides of the separation point, and significantly evolved over several tidal periods. The net production and export of vorticity into the wake, expected to sensitively depend on the interplay of tidal and low‐frequency currents, is explored here with a simple conceptual model. Application of the model to a 10‐month mooring record suggests that inclusion of high frequency oscillatory currents may boost the net flux of vorticity into the ocean interior by a depth dependent factor of 2 to 25. Models that do not represent the effect of these high frequency currents may not accurately infer the net momentum or energy losses felt where strong flows encounter steep island or headland topography. Key Point: Island wake generation is influenced by both low‐frequency and tidal flows